A comparative study of low dose magnesium sulphate therapy with Pritchard’s regime in management of Eclampsia - Kansara, Vijay M.; Patel, Payal Sureshkumar; Desai, Ajesh N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is one of the most common causes of maternal and perinatal mortality and morbidity in India. Amongst the principles of management of eclampsia, the first is the control of convulsions. Magnesium sulphate is the main stay of treatment in eclampsia and imminent eclampsia. Average weight of Indian women is less than the western women due to which lower dose of magnesium sulphate can be used. The aim of the study was to compare the efficacy of low dose magnesium sulphate regimen with standard Pritchard regimen in control of eclampsia. Methods: The study was carried out at emergency labour room, GMERS Sola Civil Hospital Ahmedabad. 120 patients of eclampsia were divided randomly into study group (n=60) receiving low dose MgSO4 and control group (n=60) receiving Pritchard regimen. The recurrence of convulsion, toxicity of MgSO4 and maternal and fetal outcome was studied. Results: It was observed that with low dose MgSO4 regime, convulsions were controlled in 91.7% of the cases. With standard Pritchard’s regime convulsions were controlled in 95% of patients. The maternal and perinatal mortality and morbidity were comparable in both groups. Conclusions: Low dose magnesium sulphate therapy is as effective as Pritchard’s regime for controlling convulsions in eclampsia and can be safely given in Indian women.